Enhancement of Islet Engraftment and Achievement of Long-Term Islet Allograft Survival by Toll-Like Receptor 4 Blockade. Issue 1 (January 2015) - Giovannoni, Laurianne; Muller, Yannick D.; Lacotte, Stéphanie; Parnaud, Géraldine; Borot, Sophie; Meier, Raphaël P.H.; Lavallard, Vanessa; Bédat, Benoît; Toso, Christian; Daubeuf, Bruno; Elson, Greg; Shang, Limin; et al.
<x xml:space="preserve">Abstract</x> Background Toll-like receptors are key players in sterile inflammation phenomena and can link the innate and adaptive immune systems by enhancing graft immunogenicity. They are also considered mediators of types 1 and 2 diabetes development. The aim of the present study was to assess the role of Toll-like receptor-4 (TLR4) in mediating the inflammatory and immune responses to pancreatic islets, thereby promoting inflammatory destruction and immune rejection of islet grafts. Methods Experiments were conducted in murine and human in vitro systems and in vivo murine islet transplant models, using species-specific anti-TLR4 monoclonal antibodies. In vitro, mixed lymphocyte-islet reaction experiments were performed to assess T-cell activation and proliferation. In vivo, both a syngeneic (B6-to-B6) marginal mass islet transplant model to assess the impact of TLR4 blockade on islet engraftment and an allogeneic (DBA1-to-B6) model were used. Results In vitro TLR4 blockade decreased lipopolysaccharide-mediated β-cell apoptosis and T-cell activation and proliferation against allogeneic islets. In vivo, TLR4 blockade resulted in significantly better syngeneic marginal mass islet engraftment and in indefinite allogeneic islet graft survival. Tolerance was not observed because donor-specific skin graft rechallenge in nonrejecting animals resulted in rejection of both skin and islets, but without accelerated rejection as compared to naive animals. Conclusion Taken together, our data indicate that TLR4 blockade leads to a significant improvement of syngeneic islet engraftment and of allogeneic islet graft survival. A mechanism of graft accommodation with concurrent inhibition of donor-specific immune memory is likely to be involved.